2014
DOI: 10.1103/physrevd.90.124026
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate regression analysis of gravitational waves from rotating core collapse

Abstract: We present a new multivariate regression model for analysis and parameter estimation of gravitational waves observed from well but not perfectly modeled sources such as core-collapse supernovae. Our approach is based on a principal component decomposition of simulated waveform catalogs. Instead of reconstructing waveforms by direct linear combination of physically meaningless principal components, we solve via least squares for the relationship that encodes the connection between chosen physical parameters and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The finite-size scaling functions f G (z, z L ), f χ (z, z L ) have been determined for the 3-D O(4) universality class in Ref. [21].…”
Section: Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The finite-size scaling functions f G (z, z L ), f χ (z, z L ) have been determined for the 3-D O(4) universality class in Ref. [21].…”
Section: Equationmentioning
confidence: 99%
“…The latter is appropriate for large L, if the volume dependence predominantly arises from regular terms and the former is appropriate close to or in the continuum limit, if the singular part dominates the partition function. In the former case, we use the approximation z δ (z L ) ∼ z 5.7 L , which parametrizes well the finitesize dependence of T δ in the scaling regime [21]. The resulting fits are shown in Fig.…”
Section: Equationmentioning
confidence: 99%
“…The correlation coefficient is always bound between −1 (strong negative correlation) and 1 (strong positive correlation). This only accounts for linear correlations, so even if two variables are tightly coupled, nonlinear relationships will reduce the magnitude of the correlation coefficient and a more involved analysis would be necessary for characterizing nonlinear relationships (see, e.g., [56]). …”
Section: Gw Correlations With Parameters and Eosmentioning
confidence: 99%
“…There are significant uncertainties in these and it is difficult to exactly predict the time series of the GW signal. Nevertheless, work by several authors [11,16,20,[149][150][151][152] has demonstrated that GW emission from rotating core collapse and bounce has robust features that can be identified and used to infer properties of the progenitor core.…”
Section: Gravitational Waves From Rotating Core Collapse and Bouncementioning
confidence: 99%